Internet Ussage and Agricultural Information Utilization by Agricultural Extension Staff in Bogor District - Novi Elian; Djuara P Lubis; Parlaungan A Rangkuti (Institut Pertanian Bogor, 2014)
Abstract The vast development of communication technology produces so many communication media that can be used to disseminate information. One of the communication media that can be used is cyberspace communication or internet media. Agricultural extension workers as those who act as diseminator supposedly able to utilize agricultural information communication technology development in carrying out their duties and functions. This study aims to description of internet usage by agricultural extension, analyze the factors affecting the level of internet usage, as well as analysis of the utilization of information and its relevance to the level of use by agricultural extension. The level of internet usage by respondents measured the frequency and duration of use is still low. Respondents use the internet less than three times a week and duration of less than three hours a day. Factors significantly correlated with the use of the Internet by agricultural extension is extension characteristics (age and availability of technology) and information needs of extension (information processing technology, marketing and climate). Utilization by agricultural extension information is stored for consumption in the form of private, shared with a fellow instructor for discussion, and distributed to farmers as extension material. More than half of the respondents utilize the information to be discussed to fellow instructor, the next disseminated to farmers and stored for personal. Keywords: Internet Ussage, Utilization of Agricultural Information, Agricultural Extension.